Influence of methods of main tillage on crop pollution and yield of spring barley in the conditions of the Left-Bank Forest Steppe - Hanhur, V.; Len, O.; Onipko, V.; Hanhur М.; Mykolenko, Kh. (Scientific Progress & Innovations, 2023)
Spring barley (Hordeum vulgare L.) is one of the most important grain fodder and food crops. The significance of this crop consists in the fact that its grain is the most balanced in amino acid composition and in this respect is not inferior to the leading cereals. The research was conducted on the experimental field of the Poltava State Agricultural Research Station named after M. Vavilov during 2022‒2023, in a short-term field experiment. According to the results of research, it was found that at initiation of the tillering phase of spring barley plants, the smallest number of weeds seedlings in the field was observed when the plants was grown on the background of moldboard tillage. Under no-shelf tillage, there was observed an increase the number of weeds in the fields by 22.3‒28.0 units/m2 or 51.0‒64.1 % compared to plowing. At the time of harvesting of spring barley, the opposite trend was noted, which indicates a decrease in the level of weed infestation of fields in the variants of flat-cut and chisel tillage by 48.8‒64.3 % compared to plowing. According to the experimental data it was found that the mass of weed plants in the air-dried condition both in the tillering phase and before harvesting was the highest in the background of plowing. In the variants of moldboardless tillage with both aggregates CHG-40 and GRS-2, a decrease in weed mass was noted, respectively, by 15.2‒45.3 and 4.8‒62.7 % and 26.8‒45.3 and 21.4‒57.8 %, compared to plowing. In the structure of biological groups of weeds, according to the variants of the main tillage, the small annual species dominated, it’s part varied from 88.1 to 97.3 %. Among the soil tillage methods, the best conditions for barley growth and development were formed on the background of chisel tillage, where the yield was maximum 5.15 t/ha. Under flat-cut tillage and plowing, the yield of spring barley grain was inferior to chiseling, respectively, by 0.16 and 0.28 t/ha. It was found that increasing the depth of cultivation from 14‒16 cm to 22‒25 cm did not significantly affect the change in crop yield. That is, the effect of different tillage depths on spring barley yields can be considered as equivalent.